EFFECT OF SUPPLIER DEVELOPMENT ON PROCUREMENT PERFORMANCE IN PUBLIC SECTOR IN KENYA: A CASE OF KENYA ELECTRICITY GENERATING COMPANY LIMITED (KENGEN) - Oromo, Fredrick A.O.; Mwangangi, Dr. Patrick (International Journal of Supply Chain Management, 2017)
Purpose: To determine the effect of supplier development on procurement performance in public sector in Kenya, a case of KenGen. Materials and methods: The study used descriptive research design and a sample size census of all 160 staff from KenGen who were provided with the questionnaires. In collecting the data, open-ended and closed-ended questions were used. The quantitative and qualitative data generated was analyzed by use of descriptive statistics feature in SPSS V.22 to generate information which was presented using tables, charts, frequencies and percentages and inferential statistics to make predictions or inferences about a population from observations and analysis of a sample using correlation analysis, regression analysis, analysis of variance (ANOVA) and coefficient analysis. Results: Results proved that creating incentives for suppliers was one way to ensure that they remain committed to a quality improvement strategy. Incentives may be in the form of a preferred supplier category with its rewards. Recommendations: In reference to supplier development, KenGen should make cooperative efforts to improve supplier capabilities with respect to technology, quality, delivery and costs as this also enhances continuous improvement and supplier capability.